2014
DOI: 10.1007/s10571-013-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Neuroprotective Activities of Hyptis suaveolens (L.) Poit. Against Oxidative Stress-Induced Neurotoxicity

Abstract: The present study was carried out to investigate the antioxidant and neuroprotective effects of Hyptis suaveolens methanol extract (HSME) using various in vitro systems. The total phenol and flavonoids contents of the HSME were quantified by colorimetric methods. The HSME extract exhibited potent antioxidant activity as determined by 2,20-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, 2,2-diphenyl-1-picrylhydrazyl, and ferric reducing antioxidant power assays. The neuroprotective activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…Reactive Oxygen Species plays an important role in oxidative damage to cellular system which leads to cell injury and death ( Ghaffari et al, 2014 ). In the presence of ROS, DCFH is oxidized to highly fluorescent dichlorofluorescein (DCF; LeBel et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive Oxygen Species plays an important role in oxidative damage to cellular system which leads to cell injury and death ( Ghaffari et al, 2014 ). In the presence of ROS, DCFH is oxidized to highly fluorescent dichlorofluorescein (DCF; LeBel et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study effect of oosporein on MMP collapse was assessed by fluorescent rhodamine 123. With decrease in MMP the intracellular rhodamine 123 dye subsequently gets released from the plasma membrane and shows decreased fluorescence ( Ghaffari et al, 2014 ). The diffusion and accumulation of rhodamine 123 in mitochondria is directly proportional to the extent of MMP ( Ubl et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that BDNF has a mechanism related to H 2 O 2 toxicity. Cells exposed to H 2 O 2 resulted in the decreased BDNF level (Huang & McNamara 2012;Ghaffari et al 2014). Moreover, several lines of evidence showed the preventive effect of BDNF on neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The total phenolic content present in these extracts was quantified by the Folin Ciocalteu reagent (FCR), using the method of Ghaffari et al [ 12 ]. Briefly, 0.2 mL of the plant extract (2 mg/mL) was added to the reaction mixture consisting of 1 mL of 10% v/v FCR and 0.8 mL of Na 2 CO 3 (0.075 mg/mL) to give a final concentration of 0.2 mg/mL of each extract.…”
Section: Methodsmentioning
confidence: 99%